RAFT dispersion polymerization of 3-phenylpropyl methacrylate with poly[2-(dimethylamino) ethyl methacrylate] macro-CTAs in ethanol and associated thermo reversible polymorphism - Pei, Y.; Dharsana, N.; Hensbergen, J.; Burford, R.; Roth, Peter; Lowe, A. (RSC Publishing, 2014)
The direct synthesis of methacrylic-based soft polymeric nanoparticles via reversible addition–fragmentation chain transfer dispersion polymerization (RAFTDP) is described. The use of poly[2-(dimethylamino)ethyl methacrylate]s, of varying average degree of polymerization ([X with combining macron]n), as the stabilizing blocks for the RAFTDP of 3-phenylpropyl methacrylate (PPMA) in ethanol at 70 °C, at various total solids contents, yielded the full spectrum of self-assembled nanoparticles (spherical and worm aggregates and polymersomes). We also demonstrate that nanoparticle morphology can be tuned simply by controlling temperature. This is especially evident in the case of worm aggregates undergoing a thermoreversible transition to spherical species – a process that is accompanied by a macroscopic degelation–gelation process.